Cervical Pap smear study and its utility in cancer screening in patients attending out-patient department in a tertiary care hospital - Garg, Paridhi; Mishra, Shweta; Divedi, Pragati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cervical cancer is one of the major causes of mortality among women worldwide. By simple pap screening test cervical cancer and its precursor lesions can be detected and treated early. The aim of the study was to determine and analyze Pap smear reports from women presenting with various gynaecological indications in a tertiary care hospital. Methods: This retrospective study was conducted in the department of obstetrics and gynaecology at Rama Medical College Hospital and Research Centre, Hapur over a period of 6 months. Patients with various complaints between ages 21 to 70 years were screened during August 2020 to January 2021 by taking Pap smear using Ayres spatula. Total 330 patients were studied. Slides were reported according to the 2014 Bethesda system. Results: Maximum number of cases were in the age group 31-40 years constituting 32.72% of the total cases followed by age group 41-50 years. Vaginal discharge was the commonest chief complaint seen in 32.12% cases followed by menorrhagia. Maximum number of cases reported as non-specific inflammatory smears (64.54%). Among epithelial cell abnormalities incidence of LSIL was 2.42% followed by ASCUS (1.82%). Conclusions: Pap smear testing is an economical, non-invasive and simple OPD procedure to detect potentially precancerous and cancerous lesions of cervix. It should be established as a routine screening procedure to reduce the treatment burden, morbidity and mortality.